KONSENTRASI LOGAM BERAT Pb, Cu dan Zn PADA AIR DAN SEDIMEN PERMUKAAN EKOSISTEM MANGROVE DI MUARA SUNGAI PORONG, SIDOARJO, JAWA TIMUR - Harlyan, Ledhyane Ika; Julinda Sari, Syarifah Hikmah (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
Porong River Estuary is potentially assumed to be contaminated of heavy metals Pb, Cu and Zn from anthropogenic and industrial activities in Sidoarjo, East Java. This study aimed to analyze the difference of heavy metal contaminations (Pb, Cu and Zn) in water and sediment of mangrove ecosystem located in Porong River Estuaries in September 2014. The location of sampling was selected by purposive sampling method considering the river parts: (1) upstream, (2) downstream and (3) open sea. Analysis of heavy metal contaminations (Pb, Cu and Zn) were performed by using Atomic Absorption Spectrophotometer (AAS). The average concentration of Pb, Cu and Zn in water were <0.0044, 0.0226 dan 0.3555 mg/kg, respectively. While those of Pb, Cu and Zn in sediments were 0.0648, 0.3543 and 0.5653 mg/kg, respectively. It showed significance different of Pb and Cu concentration in water and sediments. On the other hand, there was no difference of Zn concentration between those medium.